The Politics of Civilizing the Colony: Haji Hasan Mustapa’s Malay Guidebook on the Etiquette for Acehnese People towards the Dutch in the Netherland East Indies - Jajang A. Rohmana (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2020)
This article examines how the Dutch colonial government in the Netherland East Indies attempted to civilize its colony through the work on etiquette. It focuses its analysis on the Malay manuscript of Haji Hasan Mustapa on the code of polite behavior for Acehnese in dealing with the Dutch people, Kehormatan kepada Orang Belanda (Cod. Or. 18.097 S9). Hasan Mustapa wrote his work when he served as Chief-Penghulu of Kutaraja, Aceh (1893-1895) and sent it to C. Snouck Hurgronje in Batavia. He wrote the book at the request of Teuku Umar, an Acehnese patriot who used to collaborate with the Dutch authorities. Using a philological analysis, this study suggests that the Dutch authority utilized the native officials to write the etiquette guidebook on speaking and behavior to civilize Acehnese people. Hasan Mustapa’s work on etiquette shows that he played an important role in maintaining the Dutch honor and bridging the interests of the Dutch colonial government in its colony, the Netherland East Indies.